(untitled) (Вісник: Міжнародні відносини, 2024)
The article contains a review of scientific literature on the essence, features and functions of conspiracy theories in modern society. It is shown that conspiracy theories give alternative explanation of important events in modern society. Such theories are speculative, simplistic, biased, unprovable and irrefutable. The сonspiracy theories are manipulative and can be used by political actors to influence public opinion and behavior. The constructive or destructive role of conspiracy theories in society largely depends on the specifics of the conspiracy theory itself, the context of its emergence, and the purposes of its use by political actors.